An analysis of rural poverty alleviation programs and challenge in Assam: a micro level study of margherita block of tinsukia district - Deori, Bhupen (International research journal of management, IT and social sciences, 2015)
The research was intended to describe the development of the rural people, the country cannot claim to be a developed country. Not only India, but every developing country of the world has also been trying to the reduction of poverty because of the poverty eradication is considered an integral to humanity’s mission for their sustainable development. It is a concept of global dialog and vital for the attainment of international goals. The government of India, as well as states government, has launched some poverty eradication program for the development of rural peoples, but all these poverty alleviation programs are did not yield the desired result due to various shortcomings. Successful implementation of this program required an appropriate policy framework, adequate funds, and effective delivery mechanism. An effective and responsive district level field machinery with a high degree of commitment, motivation, professional competence, and above all integrity has been recognized as one of the pre-requisites for successful implementation of an anti-poverty strategy.